Pengaruh Efikasi Diri dan Regulasi Diri terhadap Stress Akademik Mahasiswa selama Pandemi COVID-19 - Alfi Nur Faizah; Lifa Farida Panduwinata (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
The emergence of the COVID-19 pandemic has changed the world of education, because face-to-face learning activities were stopped and the learning process shifted to using online methods. Changes in the learning process cause academic stress in students. This paper aims to describe the results of research on the effect of student self-efficacy and self-regulation on academic stress experienced by students in online courses. This study uses a quantitative approach. Data analysis used multiple linear regression with the help of SPSS version 26 for windows. The results of the study state that self-efficacy and self-regulation have an effect on student academic stress which can be seen from the calculation results obtained with a significance value of 0.000 ≤ 0.05. Then, there is a significant effect between self-efficacy and academic stress on students as seen from the calculation results obtained with a significance value of 0.000 ≤ 0.05. Furthermore, there is an influence between self-regulation and academic stress on students as seen from the calculation results obtained with a significance value of 0.007 ≤ 0.05.